Perhitungan Kerugian Infrastruktur dan Ekonomi Pasca Bencana Hidrometerologi - Ronal H. T. Simbolon; Ramadona Simbolon; Anisa Lukman (Universitas Islam Sumatera Utara, 2022)
Assessment of post-disaster damage and losses is to as soon as possible measure the scale of the disaster's impact so that priority can be determined for handling and determining strategies for reconstruction and rehabilitation. In addition, the damage and loss assessment aims to estimate the benefits of the investment that will be allocated to the community and the development of areas affected by the disaster. However, it is difficult for government institutions to calculate post-disaster losses, which can lead to asymmetric information and budget abuse. Therefore, the document for calculating infrastructure and economic losses is important in providing fast and accurate information after a hydrometeorological disaster